Surgical treatment of giant right ventricular fibroma for a newborn: A case report - Liu, Yuhang; Wang, Ning; Wen, Ping (Frontiers in Cardiovascular Medicine, 2022)
This report describes the surgical treatment of giant right ventricular fibroma in a newborn. Cardiac uhrasonography and CT showed a large mass in the right ventricle wall, which narrowed the right ventricular inflow tract. The newborn patient gradually developed symptoms such as shortness of breath, oliguria, and pericardial effusion. We performed tumor excision, but due to severe damage to the right ventricular wall and right heart failure, the patient relied on cardiopulmonary bypass. Then, we immediately restored the opening of the ductus arteriosus, enlarged the foramen ovale, and used various vasoactive drugs to ensure the smooth resuscitation of the patient. This is a kind of operation for the youngest patients. The perioperative treatment experience indicated the feasibility of excision of giant right ventricular fibroma for newborn patients.